197TiPGLOW: Zolbetuximab + CAPOX compared with placebo + CAPOX as first-line treatment for patients with Claudin18.2+/HER2– Locally advanced unresectable or metastatic gastric or gastroesophageal junction (GEJ) adenocarcinoma: A randomized phase III study. (24th November 2019) - Xu, R-H; Dongsheng, Z; Ajani, J; Al-Batran, S-E; Bang, Y-J; Catenacci, D; Enzinger, P; Ilson, D; Kim, S; Lordick, F; Shitara, K; Van Cutsem, E; et al.
Abstract: Background: Gastric cancer (GC) is the fourth leading cause of cancer death worldwide, with disproportionate incidence and mortality rates reported for people from Eastern Asia. Capecitabine + oxaliplatin (CAPOX) is a standard first-line treatment for advanced GC. Recently, Claudin (CLDN)18.2 has emerged as a promising targetable biomarker. In healthy tissue, CLDN18.2 is confined to gastric mucosa tight junctions. Upon malignant transformation, cell polarity perturbations lead to exposure of CLDN18.2 on the cell surface. Zolbetuximab is a chimeric IgG1 monoclonal antibody that specifically binds to CLDN18.2 and mediates cell death through antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity. In a randomized phase 2 study (NCT01630083), patients with CLDN18.2 + advanced GC/GEJ treated with zolbetuximab + epirubicin, oxaliplatin, and capecitabine (EOX) showed prolonged survival compared with EOX alone. Trial design: This phase 3, double-blind, placebo-controlled study (NCT03653507) will enroll ∼500 adult patients from global sites, including sites in China, Japan, Republic of Korea, and Thailand. Patients with CLDN18.2 + /HER2 – locally advanced unresectable or metastatic GC or GEJ not previously treated with chemotherapy will be eligible. Patients will be randomized 1:1 to receive zolbetuximab + CAPOX or placebo + CAPOX. Zolbetuximab will be administered as an 800-mg/m 2 IV loading dose followed by 600 mg/m 2 Q3W in combination with CAPOX. Central testing of tumor tissue will determine CLDN18.2 and HER2 status (if unknown); patients will be considered CLDN18.2 + if ≥ 75% of tumor cells demonstrate moderate-to-strong membranous IHC staining. The primary objective is to compare progression-free survival of zolbetuximab + CAPOX vs placebo + CAPOX. The key secondary efficacy endpoint is overall survival. Objective response rate, duration of response, the safety/tolerability profile, PK profile, and immunogenicity of zolbetuximab are other secondary endpoints. Clinical trial identification: NCT03653507. Legal entity responsible for the study: Astellas Pharma US, Inc. Funding: Astellas Pharma US, Inc. Disclosure: J. Ajani: Advisory / Consultancy, Research grant / Funding (institution): Astellas. S-E. Al-Batran: Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Lilly; Advisory / Consultancy: Merck; Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche; Advisory / Consultancy: SERVIER; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Celgene; Speaker Bureau / Expert testimony: Nordic Bioscience ; Research grant / Funding (institution): Hospira; Research grant / Funding (institution): Medac; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Roche Pharma AG; Research grant / Funding (institution): Vifor Pharma. Y-J. Bang: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): Genetech/Roche; Advisory / Consultancy, Research grant / Funding (institution): MSD; Advisory / Consultancy, Research grant / Funding (institution): Merck Serano; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Speaker Bureau / Expert testimony, Research grant / Funding (institution): BMS; Advisory / Consultancy, Research grant / Funding (institution): Eli Lilly; Advisory / Consultancy: Taiho; Advisory / Consultancy, Research grant / Funding (institution): Daiich-Sankyo; Advisory / Consultancy, Research grant / Funding (institution): Astellas; Advisory / Consultancy, Research grant / Funding (institution): BeiGene; Advisory / Consultancy, Research grant / Funding (institution): GreenCross; Advisory / Consultancy: Samyang Biopharm; Advisory / Consultancy: Hanmi; Advisory / Consultancy, Research grant / Funding (institution): Genexine; Research grant / Funding (institution): GSK; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): MacroGenics; Research grant / Funding (institution): Boston Biomedical. D. Catenacci: Honoraria (self), Advisory / Consultancy: Astellas; Honoraria (self), Advisory / Consultancy: Merck; Honoraria (self), Advisory / Consultancy: BMS; Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: Gritstone; Honoraria (self), Advisory / Consultancy: Taiho; Honoraria (self), Advisory / Consultancy: Genentech/Roche; Honoraria (self), Advisory / Consultancy: Daichii Sankyo. P. Enzinger: Advisory / Consultancy: Merck; Advisory / Consultancy: Astellas; Advisory / Consultancy: Celgene; Advisory / Consultancy: Lilly; Advisory / Consultancy: Loxo; Advisory / Consultancy: Taiho. D. Ilson: Honoraria (self): Astellas. S. Kim: Advisory / Consultancy: Astellas. F. Lordick: Advisory / Consultancy: Astellas; Research grant / Funding (institution), Travel / Accommodation / Expenses: BMS; Advisory / Consultancy: AstraZeneca. K. Shitara: Advisory / Consultancy, Research grant / Funding (institution): Astellas Pharma; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: Takeda; Advisory / Consultancy: Pfizer; Advisory / Consultancy, Research grant / Funding (institution): Ono Pharmaceutical; Honoraria (self): Novartis; Honoraria (self): AbbVie; Honoraria (self): Yakult; Research grant / Funding (institution): Dainippon Sumitomo Pharma; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): Taiho Pharmaceutical; Research grant / Funding (institution): Chugai Pharma; Advisory / Consultancy, Research grant / Funding (institution): MSD; Research grant / Funding (institution): Medi Science. E. Van Cutsem: Advisory / Consultancy: Astellas; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (institution): Celgene; Advisory / Consultancy: Incyte; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy, Research grant / Funding (institution): Merck Sharp & Dohme; Advisory / Consultancy, Research grant / Funding (institution): Merck KGaA; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Servier; Research grant / Funding (institution): Amgen; Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): Ipsen. A. Arozullah: Full / Part-time employment: Astellas. J. Wook Park: Full / Part-time employment: Astellas Pharma Global Development Inc. All other authors have declared no conflicts of interest.